Rosemary Radford Ruether : themes from a feminist liberation story - Ackermann, Denise (Scriptura, 2008)
As one of the earliest and most influential feminist liberation theologians, Rosemary Radford Ruether's oeuvre has enabled many women theologians in different contexts and cultures to cover new ground by drawing on her insights. This article is a tribute to her ground-breaking work and her far ranging interests, all under girded by her passion for justice. In order to tell aspects of her theological story, three themes are dealt with : Feminist theology according to Ruether, feminist theological methodology, and church and ministry. In conclusion, a brief assessment of her work is made with particular reference to the categories of experience, the prophetic-liberating tradition and issues of gender race and ecumenism